Migrant Labor Determinants: Do Socio-Economic Factors Affect? - Haer, Jamhul; Yuniarti, Dini (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2023)
This study aims to determine the social and economic variables that influence workers to become migrant workers. This research was conducted in Central Lombok Regency, West Nusa Tenggara. As a sample in this study, we surveyed 100 people, consisting of 50 ex-migrant workers and 50 local workers. The analytical tool used was logit analysis. The estimation results show that the influential social variables are gender, age, marital status, and education. Economic variables that affect former migrant workers include ownership of savings, ownership of loans, ownership of agricultural land, and ownership of livestock, all of which have a negative effect. The policy implications of this research are the need for new regulations or revisions to previous regulations to improve human resources at the time of pre-placement. This regulation should involve training in language skills and the abilities required for the relevant field of work to increase competitiveness. Furthermore, policies to empower migrant workers post-placement should be implemented to provide more significant opportunities and support for working or starting businesses in their home countries.JEL Classification: J61, O15How to Cite:Haer, J., & Yuniarti, D. (2023). The Migrant Labor Determinants: Do Socio-Economic Factors Affect?. Signifikan: Jurnal Ilmu Ekonomi, 12(1), 117-130. https://doi.org/10.15408/sjie.v12i1.31274.